International Nano Letters - Ghaderi, Atefeh
The overall aim of the International Nano Letters is to bring science and applications together on nanoscale and nanostructured materials with emphasis on synthesis, processing, characterization, and applications of materials containing true nanosize dimensions or nanostructures that enable novel/enhanced properties or functions. It is directed at both academic researchers and practicing engineers. International Nano Letters is covering fundamental and applied research in all disciplines of science, engineering and medicine. INL publishes all aspects of nanoscale science and technology dealing with materials synthesis, processing, nanofabrication, nano-polymer, nano-catalyst, nano-particles, nano-probes, spectroscopy, properties, biological systems, nano-structures, theory and computation, nano-electronics, nano-optics, nano-mechanics, nano-devices, nano-detection, nano-biotechnology, nano-medicine, nano-drug delivery, nano-toxicology. All articles should emphasize original results relating to experimental, theoretical, computational, and/or applications of nanomaterials. All contributions will be peer reviewed and published free of charge after acceptance.